Genome-wide identification and expression analysis of the cryptochromes reveal the CsCRY1 role under low-light-stress in cucumber - Cao, Haishun; Wang, Rui; Zhao, Junhong; Shi, Liangliang; Huang, Yuan; Wu, Tingquan; Zhang, Changyuan (Frontiers in Plant Science, 2024)
Low-light-stress is a common meteorological disaster that can result in slender seedlings. However, the evaluation of cucumber's tolerance to low-light-stress has been inadequate. Here, we found that light treatment below 40 μmol m -2 s -1 can quickly and effectively induce low-light-stress phenotype at the early seedling stage of cucumber. Through employing this method, we successfully and quickly identified a cucumber variety that exhibited remarkable tolerance to low-light-stress. Meanwhile, we discovered that the primary cause of low-light-stress in cucumber is the reduction of blue light intensity. As we all know, the photoreceptors play a crucial role in perceiving and regulating plants' tolerance to low-light-stress. Therefore, a total of 11 photoreceptor genes were identified and evaluated. Among them, the cryptochrome 1 (CRY1) had the highest expression level and was only induced in the low-light sensitive cucumber. The CsCRY1 protein has lost 70 amino acids at the end of the Cterminal cryptochrome carboxyl terminus domain (CCT). Moreover, the CRY2 gene was not detected in all cultivated cucumbers. Through single-molecule long-read sequencing and transcriptome analysis, we also found that the alternative 5′ splice sites in the last intron of CsCRY1 result in the production of five distinct full-length splicing variants. Among them, CsaV3_3G047490.1, which was predicted to encode the CsCRY1 protein in the reference genome, was also induced by low-light-stress.These results provide crucial insights for the future exploration and utilization of CsCRY1 in cucumber.